PENGARUH ASET PAJAK TANGGUHAN, PROFITABILITAS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN COSTUMER NON CYCLICAL YANG TERDAFTAR DI BEI PERIODE 2012-2021 - Yulia Maulina; Ade Imam Muslim (Jurnal Akuntansi dan Keuangan (JAK), 2023)
This study aims to analyze the effect of deferred tax assets and profitability on earnings management in non-cyclical customer companies listed on the IDX period 2012-2021. Deferred tax assets are measured by comparing the difference between the deferred tax assets of period t and period t-1 with the deferred tax assets of period t and profitability is measured by the ratio of return on assets. Meanwhile, discretionary accruals are used as a proxy for earnings management. The method used in this research is descriptive and verification method. The population in this study is the financial statements of non-cyclical customer companies listed on the IDX period 2012-2021. The sample in this study were 21 non-cyclical customer companies selected using purposive sampling. The results of this study indicate that simultaneously deferred tax assets and profitability affect earnings management. Partial research on deferred tax assets has a significant negative effect on earnings management while profitability partially has a significant positive effect on earnings management.